Better with Bologna? Tertiary education reform and student outcomes. Issue 4 (4th July 2019) - Hahm, Sabrina; Kluve, Jochen
ABSTRACT: Given the scale of the university reform induced by the Bologna Process, little is known about how the reform impacted those most immediately affected: the students. This paper uses unique micro data from Humboldt-Universität zu Berlin, Germany, to estimate treatment effects on student outcomes. Variation in treatment introduction over time and across subjects generates exogenous assignment of students into treatment (Bachelor) and control groups (Diploma). Results indicate that the Bologna reform led to a significant, sizeable increase in the probability of graduating within planned instructional time; it also decreased standardized study duration and worsened final grades in the treatment group.